Preparation for practice: a novel role for general practice in pre-foundation assistantships. Issue 4 (4th July 2017) - Ryan, Peter S. J.; Gormley, Gerard J.; Hart, Nigel D.
Abstract: Background: Hospital-based undergraduate assistantships are now widely established in medical school curricula. They are considered to improve graduates' preparedness for practice in their role as a foundation doctor. Foundation doctors play a key team role in ensuring patient safety during complex transitions across the hospital/primary care interface, and their self-reported preparedness for practice still varies considerably. Aims: We sought to explore what spending one week of the pre-foundation assistantship in General Practice might add. Methods: We solicited reflective audio diaries from final year students during a one-week pilot attachment delivered during the post-finals, pre-foundation assistantship period, and performed an iterative thematic analysis on the acquired data. Results: From this attachment in General Practice, students described diverse learning, resulting in improved preparedness for (hospital) foundation practice across several domains, impacting positively on how they might approach patients in the future. Self-confidence improved due to affirming outcomes and tutor mentorship. Students deepened their understanding of community healthcare and General Practice; and seeing the 'Patient Journey' across the interface from the patient's perspective helped them contextualise their forthcoming role as foundation doctors in managing it. Discussion: We believe that this novel intervention distinctively contributed to preparedness for practice. It aligns with published recommendations about extending the current assistantship model. We suggest it should be incorporated more widely into pre-foundation assistantship curricula.